2019
DOI: 10.1002/smll.201902313
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Channels in an Infectious Biofilm Created by Magnetic Nanoparticles Enhanced Bacterial Killing by Antibiotics

Abstract: The poor penetrability of many biofilms contributes to the recalcitrance of infectious biofilms to antimicrobial treatment. Here, a new application for the use of magnetic nanoparticles in nanomedicine to create artificial channels in infectious biofilms to enhance antimicrobial penetration and bacterial killing is proposed. Staphylococcus aureus biofilms are exposed to magnetic‐iron‐oxide nanoparticles (MIONPs), while magnetically forcing MIONP movement through the biofilm. Confocal laser scanning microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 25 publications
0
67
0
Order By: Relevance
“…Bacterial infections are a major public heath challenge worldwide, and are estimated to be the primary cause of disease‐related mortality by year 2050. [ 7 ] The emergence of drug resistant strains due to antibiotics overuse has greatly limited the efficacy of currently available drugs. [ 7,8 ] Therefore, novel strategies are needed that can effectively clear bacteria without inducing resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial infections are a major public heath challenge worldwide, and are estimated to be the primary cause of disease‐related mortality by year 2050. [ 7 ] The emergence of drug resistant strains due to antibiotics overuse has greatly limited the efficacy of currently available drugs. [ 7,8 ] Therefore, novel strategies are needed that can effectively clear bacteria without inducing resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] The emergence of drug resistant strains due to antibiotics overuse has greatly limited the efficacy of currently available drugs. [ 7,8 ] Therefore, novel strategies are needed that can effectively clear bacteria without inducing resistance. Previous studies have shown that an endogenous biological energy source can generate hydrogen peroxide (H 2 O 2 ) in the inflamed region and kill the infiltrating pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,12 ] By rupturing the biofilm matrix, the protective layer is removed and planktonic cells are released into the surrounding medium, which are far easier targets for the majority of antimicrobial agents. While there has been limited research into this area, the studies which investigate nanomaterials for magnetophysical antimicrobial activity have utilized vastly different methods, including gold‐iron microrods, [ 277 ] Fe 3 O 4 nanoparticles in combination with additional antimicrobial agents, [ 278–280 ] aggregated Fe 3 O 4 particles, [ 281 ] and gallium alloy‐iron liquid metal droplets. [ 282 ] The mode‐of‐action of these materials varies greatly, as such this review will introduce the concept behind each technology.…”
Section: Magnetic Activated Antimicrobial Metal Nanomaterialsmentioning
confidence: 99%
“…Quan et al used iron oxide nanoparticles (278 ± 61 nm) as a method to magnetically create artificial channels in the biofilm to allow enhanced dissemination of antimicrobial agents within the biofilm ( Figure ,i). [ 278 ] Two strains of S. aureus , differentiated by their ability to produce EPS, were allowed to grow into a mature biofilm, after which they were treated with iron oxide nanoparticles and varying concentrations of gentamicin. Following treatment, there was an observed four to sixfold reduction in viable cells in the presence of gentamicin (1250 µg mL −1 ) and magnetically activated iron oxide nanoparticles, compared to the gentamicin on its own.…”
Section: Magnetic Activated Antimicrobial Metal Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation